Assessing the Influence of Market Orientation Dimensions on SMEs Sustainability in Nigeria: An Importance Performance Map Analysis Approach - Adeola E. Adetayo; Adebiyi J. Abosede; Moruff S. Oladimeji; Waliu M. Adegbite (Lembaga Penerbit Fakultas Ekonomi dan Bisnis Universitas Trisakti, 2024)
Sustainability beyond the incubation period is a major challenge for small and medium-sized enterprises (SMEs), hindering their potential for job creation and economic growth. Research shows that market orientation can significantly impact SMEs' sustainability, but there is limited evidence on how its dimensions contribute, individually and collectively, to long-term success, especially in developing countries like Nigeria. This study explores how different dimensions of market orientation contribute to the sustainability of SMEs in Nigeria. A total of 228 SME owners and managers were selected in Ogun State using a non-parametric sampling approach. Importance-Performance Map Analysis (IPMA) was used to evaluate how each dimension of market orientation contributes to SME sustainability. The results show that market responsiveness has the highest performance score of 69.18 and an importance score of 0.276. Intelligence dissemination has a performance score of 71.16 but is not a key determinant, with a negative importance score of -0.123. Competitor orientation, customer orientation, inter-functional coordination, market responsiveness, and value creation are all in the fourth quadrant, emphasizing their importance for SME sustainability. This study suggests SME owners prioritize high-importance and performance dimensions and improve those with lower levels for sustainability.